The Effect of Profitability and Sales Growth on Tax Avoidance With Profit Management as a Moderating Variable in Food & Beverage Companies Listed on the Indonesia Stock Exchange - Najwan Fauzi Haris; Yanuar Ramadhan (Dinasti Publisher, 2025)
This study aims to examine whether profitability and sales growth have an impact on tax avoidance, with earnings management as a moderating variable in the food & beverage sector companies listed on the Indonesia Stock Exchange. The study uses a sample of 12 food & beverage companies listed on the Indonesia Stock Exchange for the period 2014-2023. The purposive sampling technique was applied, and multiple regression analysis was used to test the hypotheses. Data were analyzed using Eviews 13 software to identify the research model and discuss the results. The findings indicate that sales growth significantly affects tax avoidance, while profitability and earnings management have a significant impact on tax avoidance. Furthermore, the interaction between sales growth and earnings management also significantly affects tax avoidance. Based on these findings, companies should pay close attention to earnings management to avoid excessive tax avoidance practices, especially with rapid sales growth. On the other hand, these results suggest that stricter tax policies and more intense supervision by the government can limit companies' ability to engage in tax avoidance.